Kinetics of electron transfer between cardiac cytochromes c1 and c. - Kim, C H (1984)
Highly purified cytochrome c1, which consists of only one heme peptide and does not form a stable c1-c complex (c1-H-c complex), was used in studies of electron transfer between cytochrome c1 and c. Results show that a stable and ionic-strength-sensitive c1-c complex (i.e., the c1-H-c complex) in the forms of the various oxidation states is not required, in contrast to the current belief of the participation of the complex in the electron transfer between cytochromes c1 and c. A minimum mechanism for electron transfer between these two cytochromes is suggested in accord with the experimental results.